The Influence of Transformational Leadership, Work Culture, and Human Resource Quality on Employee Performance at the Ministry of Defense of the Republic of Indonesia: A Study in the Field of Planning - Sianturi, Christopher H.; Maryani, Dedeh; Soemartono, Triyuni; Rachmatsyah, T. Herry (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2026)
The Ministry of Defense of the Republic of Indonesia (Kemhan RI) is required to ensure optimal employee performance in the face of an increasingly complex strategic defense environment. Various factors, including transformational leadership, work culture, and the quality of human resources influence this performance. This study aims to analyze the influence of these three variables on employee performance within the Ministry of Defense of the Republic of Indonesia. The study employs a mixed methods approach by integrating quantitative and qualitative data to achieve a comprehensive understanding. The study population consists of 227 employees, with a sample of 145 respondents selected via random sampling using the Slovin formula. Data were collected through questionnaires and interviews, then analyzed using SPSS 24 via validity and reliability tests, t-tests, and simple regression. The results indicate that transformational leadership, work culture, and human resource quality significantly influence employee performance. These findings confirm that improving performance requires an integrated approach through strengthening leadership, fostering an adaptive work culture, and continuously enhancing human resource competencies. This study recommends that the Indonesian Ministry of Defense develop transformational leadership programs, strengthen a collaborative work culture, and improve human resource quality through continuous training to support organizational performance effectiveness.